Research of inter-phase interaction in ZOL-silicate paints - V.I, Loganina; E.B, Mazhitov (International Journal of Engineering and Technology, 2018)
It was suggested to use polysilicate solutions obtained by mixing liquid glass and silicic acid sol as a binder in the manufacture of sili- cate paints. Information is provided on the mechanism for increasing the operational properties of coatings based on sol silicate paint. It has been revealed that polysilicate solutions form membranes characterized by higher tensile strength due to an increase in the fraction of high-polymer fractions of silicic anions in the structure of the polysilicate binder in comparison with liquid glass. The results of a study on the interphase interaction between the pigment and the film-forming agent are given. It is shown that potassium polysilicate solutions form a smaller contact angle on the surface of the pigment (filler) and are characterized by greater work of wetting and adhesion to the filler (pigment).